Side predilection in congenital anomalies of the kidney, urinary and genital tracts. Issue 6 (December 2020) - Kirkpatrick, Joshua; Upadhyay, Vipul; Mirjalili, S. Ali; Taghavi, Kiarash
Summary: Background: There appear to be various patterns of sidedness with relation to the common urogenital malformations observed in pediatric urology. The objective of this statistical review was to synthesize this data and to assess if these patterns are significant. Materials and methods: Eighteen urogenital conditions were investigated and for each condition the five largest studies that noted laterality were included. The sidedness of each condition was then analysed for statistical significance. Results: Three conditions had a statistically significant higher proportion on the right side: palpable undescended testis (63%, p = 0.0002), inguinal hernia (59%, p = 0.0001) and hydrocele (60%, p = 0.003). Three conditions were significantly more common on the left side: impalpable undescended testis (59%, p = 0.0008), renal agenesis (54%, p = 0.02) and vesico-ureteric junction obstruction (71%, p < 0.0001) while both pelvi–ureteric junction obstruction (62%, p = 0.09) and absent vas deferens (61%, p = 0.11) were trending towards significance. Conclusions: Various urogenital malformations display a predilection for one side. Proximal malformations tend to be more frequently seen on the left side, where as inguinoscrotal malformations are more frequently observed on the right. There is an increasing body of literature regarding aetiological factors for these conditions. However, our current understanding of the pathophysiology of these conditions does not completely explain this pattern of observation.